News in the algorithmic media landscape: a signifying practice - Bengtsson, Stina (Anais de Resumos Expandidos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais; Vol 1 No 5 (2022): Anais de Resumos Expandidos V Seminário Internacional de Pesquisas em Midiatização e Processos Sociais, 2022)
In this paper I approach news use from the perspective of young Swedish audiences, and the cultural form news takes in today’s digital landscape. The analysis builds on an interview study conducted in Sweden between October 2019 and January 2021 as part of a larger research project on news perceptions and practices among young adults (18-26 years old). For this analysis I am returning to the theoretical concept of signifying practice (Williams, 1981; Hall, 1997), emphasising not only the routinised dimensions of media practices, but also their role in meaning making. Culture is, according to Stuart Hall (1980) “itself a practice—a signifying practice—and had its own determinate product: meaning” (p. 18). Understanding news as a signifying practice emphasise not only the mundane and routine aspects of news, but also the meaning-making processes involved in news use, emphasising news also as text and content.